PENGARUH KREDIBILITAS INFLUENCER PADA EFEKTIVITAS IKLAN MEDIA SOSIAL INSTAGRAM DALAM MEMBENTUK MINAT BELI KONSUMEN (STUDI PADA PENGIKUT INSTAGRAM AYUDIA BING SLAMET) - Alhensa Ferninda Jelita; Hasnah Rimiyati (Universitas Ahmad Dahlan, 2021)
This study aims to analyze the influence of influencers' credibility on the effectiveness of Instagram social media advertising in shaping consumer buying interest (Study on Instagram followers Ayudia Bing Slamet). The subjects in this study were students using social media Instagram who were in the Special Region of Yogyakarta. This research was conducted with a sample size of 200 respondents who were determined by sampling technique using non probability sampling technique with purposive sampling method and distributing questionnaires to respondents using Google Forms. The analytical tool used is Structural Equation Modeling (SEM) with the AMOS 24 application program. Based on the analysis, it was found that the attractiveness of influencers had a positive effect on consumer attitudes towards advertising, trustworthiness towards influencers had a positive effect on consumer attitudes towards advertising, influencer expertise had a positive effect on consumer attitudes towards advertising, and attitudes towards advertising had a positive effect on buying interest.